2018
DOI: 10.1007/s40430-017-0951-1
|View full text |Cite
|
Sign up to set email alerts
|

A study on fish eggs and larvae drifting in the Jirau reservoir, Brazilian Amazon

Abstract: Jirau hydropower plant (Jirau HPP) is one of the largest scale run-of-river hydro-projects in the Madeira River, Brazilian Amazon. This project has attracted strong national and international attention, especially with respect to environmental issues, because the Madeira River supports a diverse fish species. Many of these are migratory species and impact the reproductive stocks of the fishes that live in the Amazon River. Numerical simulations to predict fish eggs and larvae drift have been scarce in hydropow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…For the flow rate of 40,892 m³ s -1 , it reaches a velocity of 2.4 m s -1 close to the surface and a distance of approximately 90 m from the riverbank to the middle of the river ( Figure 11A). In their study, Barros and Rosman (2018) found results of superficial velocities (0.1 to 3.0 m s -1 ), for the month of greatest peak flow, similar to this one. Simulated mean velocities are 2.21 m s -1 and 0.44 m s -1 , and the observed mean velocities recorded in the Palmeiral station are 2.26 m s -1 and 0.46 m s -1 , respectively.…”
Section: Main Tributaries Of the Amazon Riversupporting
confidence: 60%
“…For the flow rate of 40,892 m³ s -1 , it reaches a velocity of 2.4 m s -1 close to the surface and a distance of approximately 90 m from the riverbank to the middle of the river ( Figure 11A). In their study, Barros and Rosman (2018) found results of superficial velocities (0.1 to 3.0 m s -1 ), for the month of greatest peak flow, similar to this one. Simulated mean velocities are 2.21 m s -1 and 0.44 m s -1 , and the observed mean velocities recorded in the Palmeiral station are 2.26 m s -1 and 0.46 m s -1 , respectively.…”
Section: Main Tributaries Of the Amazon Riversupporting
confidence: 60%
“…In the SisBaHiA, two groups of boundary conditions are possible through closed boundary nodes for imposing water discharges values and open boundary nodes for free surface elevations values [54]. In the open boundary a water surface elevation series was imposed to represent the waves.…”
Section: ∂U ∂T + U ∂Umentioning
confidence: 99%
“…This model system was adopted for its applications versatility and its proven reliability in the face of extensive use in various researches, projects and studies to support environmental management of water resources, which are listed in the items "Research -Theses" and "Applications -Projects" on the website. In addition to the works listed on this website, there are papers published in journals such as Feitosa et al 2013 2017, Barros and Rosman (2018) and Cunha et al(2018). The models implemented therein can be used to predict the flow of water and the transport of scalar quantities of interest.…”
Section: Computational Model Adoptedmentioning
confidence: 99%
“…In all computational simulations of this work the wind was considered variable in time and varied in space. Wind data were obtained from the ERA-Interim reanalysis model of the European Centre for Medium-Range Weather Forecasts -ECMWF (2017), available in ER-Interim Daily, which includes wind data since 01/1979. The minimum interval between available data at the time of this study is 6 hours.…”
Section: Windsmentioning
confidence: 99%